O papel das amizades na vida da mulher diante de experiências de violência por parceiro íntimo - Luque, Marjhorie Bocchi (Universidade Federal de São Carlos, 2025)
Friendship is an important source of well-being, providing social support and shared experiences. In intimate partner violence (IPV) contexts, a woman's support network may weaken, leading to social isolation and making it harder to seek help. This study aimed to investigate the functions of friendship, comparing women who were victims and non-victims of IPV, as well as those who cohabited or did not cohabit with their partners, and to analyze the relationship between types of violence experienced and friendship functions. A total of 118 cisgender women participated, aged between 18 and 44 years (M=23.5; SD=4.2). All participants completed the McGill-UFRGS Scale and the adapted version of the WHO VAW Study instrument. Results indicated that participants evaluated their friendships positively, citing more female than male friends. The most valued friendship functions were help, self-validation, and intimacy. No significant differences were found between IPV victims and non-victims, nor between those who cohabited and those who did not. Women who cohabited reported higher levels of emotional violence and total IPV scores. A weak but significant negative correlation was found between reliable alliance and emotional violence, as well as total IPV scores, suggesting that having loyal friendships may serve as a protective factor. The study highlights the importance of strengthening intimate friendships among women experiencing IPV.
The role of friendships in women's lives in the face of intimate partner violence
Keywords: Violência por parceiro íntimo; Amizades; Mulheres; Intimate partner violence; Friendship; Women; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA